Composite powder with core-shell structure as well as preparation method and application of composite powder
The core-shell structure nickel-clad aluminum composite powder is prepared by combining ultrasonic chemistry and high-pressure liquid phase reduction, which solves the problems of complex process, high cost and poor product stability in the prior art, and realizes the stability of product performance and wide application in the spraying field.
Patent Information
- Application Number
- CN202311807812.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2023-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing preparation methods for nickel-clad aluminum composite powder have problems such as complex process, high cost and poor product stability. Especially in the electroless plating method, aluminum powder is unstable in acidic or alkaline environments, making it difficult to obtain products.
The core-shell structure nickel-clad aluminum composite powder is prepared by combining ultrasonic chemistry and high-pressure liquid phase reduction. By sonicating the aluminum powder in an alkaline solution, the oxide layer and impurities are removed, and the liquid phase reduction reaction is carried out under high pressure conditions to form a uniform nickel layer.
It realizes the stability and customization of product performance, the process is simple and easy to scale, and the interface bonding strength between nickel and aluminum is improved, making it suitable for a wide range of spraying applications.
Smart Images

Figure BDA0004630763710000141 
Figure BDA0004630763710000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation, and relates to a core-shell structure composite powder and a preparation method and application thereof. Background Art
[0002] Nickel-coated aluminum composite powder is a kind of tightly combined nickel-coated aluminum composite powder with aluminum powder as the core and a layer of metal nickel coated on its surface. The core-shell structure nickel-coated aluminum composite powder prepared by the present invention is widely used in many fields such as railway, aviation, electric power, chemical industry, petroleum, automobile, metallurgy, etc., and can be used as thermal spraying material, metal-ceramic composite material, organic chemical catalyst, high-temperature alloy powder molding material, solid fuel, electromagnetic shielding conductive filler, etc.
[0003] Since the 1960s, nickel-coated aluminum composite powder has been widely used in the field of plasma spraying and flame spraying technology. The principle is that during spraying, nickel and aluminum can produce a strong alloying exothermic reaction to form an intermetallic compound NixAly. The exothermic reaction process will generate a large amount of heat, and this exothermic reaction can continue to reach the surface of the metal substrate to be sprayed, forming a firm coating on the surface of the metal substrate. The formed coating has the characteristics of a high melting point, good heat resistance and oxidation resistance. The expansion coefficient of the formed nickel-aluminum intermetallic compound is between the expansion coefficients of the base metal and the metal ceramic coating, and it is an excellent intermediate transition layer material. For example, the nickel-coated aluminum coating is used as the bottom layer of ceramic coatings such as alumina, which can greatly improve the bonding strength and thermal shock resistance of the ceramic layer. Therefore, it has broad application prospects, especially in the field of spraying.
[0004] Nickel-coated aluminum powder can be prepared by physical and chemical methods. The physical method mainly refers to the vapor deposition method, and the chemical method mainly refers to the chemical plating method. The vapor deposition process is relatively complicated and the cost is high. Although the chemical plating method is low in cost, aluminum powder is an amphoteric metal with high surface activity and is unstable in acidic or alkaline environments. Therefore, aluminum powder is very easy to dissolve in plating solutions with excessive acid, alkaline, and high temperature, which leads to poor stability of the entire chemical plating system and it is not easy to obtain stable products. Summary of the invention
[0005] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a core-shell structure composite powder and a preparation method and use thereof.
[0006] In a first aspect, the present invention provides a core-shell structure composite powder, wherein the core-shell structure composite powder is a core-shell structure nickel-coated aluminum composite powder, and the core-shell structure composite powder comprises an inner core aluminum powder and an outer shell nickel layer coated on the surface of the inner core aluminum powder.
[0007] The present invention utilizes a nickel layer to coat aluminum powder. During spraying, nickel and aluminum can produce a strong alloying exothermic reaction and can form a strong coating on the substrate surface in a metallurgical bonding manner. Therefore, the core-shell structure composite powder of the present invention is particularly suitable for application in the field of spraying and has broad application prospects.
[0008] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0009] Preferably, the core aluminum powder includes at least one of spherical particles, quasi-spherical particles, rod-shaped materials or flake-shaped materials.
[0010] Preferably, the diameter of the spherical particles is 1-125 μm, for example, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm or 125 μm, etc., preferably 5-120 μm, and more preferably 8-105 μm.
[0011] Preferably, the diameter of the spherical particles is 1-125 μm, for example, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm or 125 μm, etc., preferably 5-120 μm, and more preferably 8-105 μm.
[0012] Preferably, the diameter of the rod-shaped material is 1-125μm, for example, 1μm, 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm or 125μm, etc., preferably 5-120μm, and more preferably 10-110μm.
[0013] Preferably, the length of the rod-shaped material is 1-200μm, for example, 1μm, 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 160μm, 165μm, 170μm, 180μm, 190μm or 200μm, etc., preferably 10-160μm, more preferably 10-130μm.
[0014] Preferably, the diameter of the sheet material is 1-125μm, for example, 1μm, 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm or 125μm, etc., preferably 5-120μm, and more preferably 10-110μm.
[0015] Preferably, the thickness of the sheet material is 1-20 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 7.5 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 15 μm, 16 μm, 18 μm or 20 μm, etc., preferably 2-15 μm, and more preferably 5-10 μm.
[0016] Preferably, the shell nickel layer is evenly coated on the surface of the core aluminum powder.
[0017] Preferably, the core-shell structure composite powder is completely coated, the nickel layer is uniform and has good bonding strength and fluidity.
[0018] Preferably, the mass percentage of the inner core aluminum powder to the core-shell structure composite powder is 4-98%, for example, 4%, 6%, 8%, 10%, 12%, 15%, 17%, 20%, 23%, 26%, 30%, 33%, 35%, 36%, 38%, 40%, 42%, 46%, 50%, 53%, 55%, 58%, 60%, 63%, 66%, 68%, 70%, 73%, 75%, 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95% or 98%, etc.
[0019] Preferably, the mass percentage of the shell nickel layer in the core-shell structure composite powder is 2-96%, for example, 2%, 4%, 6%, 8%, 10%, 12%, 15%, 17%, 20%, 23%, 26%, 30%, 33%, 35%, 36%, 38%, 40%, 42%, 46%, 50%, 53%, 55%, 58%, 60%, 63%, 66%, 68%, 70%, 73%, 75%, 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95% or 96%, preferably 20-95%.
[0020] In a second aspect, the present invention provides a method for preparing the core-shell structure composite powder as described in the first aspect, wherein the core-shell structure composite powder is prepared by a method combining sonochemistry and high-pressure liquid phase reduction, and the method comprises the following steps:
[0021] (1) Aluminum powder pretreatment: placing aluminum powder in an alkaline solution for ultrasonic treatment to obtain pretreated aluminum powder;
[0022] (2) mixing the pretreated aluminum powder with an ammonium salt, a nickel salt, an optional additive and a solvent, adjusting the pH, and obtaining a reaction solution;
[0023] (3) The reaction solution is transferred to a high-pressure container, and a high-pressure liquid-phase reduction reaction is carried out under the condition of introducing a reducing gas to obtain the core-shell structure composite powder.
[0024] In the present invention, "optional additives" means that the method of the present invention may or may not use additives. If additives are used, the additives are added in step (2); if additives are not used, the additives are not added in step (2).
[0025] In the method of the present invention, an alkaline solution (such as a low-concentration sodium hydroxide solution) is used for ultrasonic treatment. During this process, the aluminum powder is washed and ultrasonicated, which can better remove the oxide layer and impurities on the surface of the aluminum powder, improve the coating effect of the surface nickel, make the nickel metal coating on the surface more uniform, and increase the interface bonding strength between nickel and aluminum.
[0026] The present invention adopts a method combining ultrasonic chemistry and high-temperature liquid phase pressure reduction reaction to prepare core-shell structure nickel-coated aluminum composite powder. The prepared product has stable performance, can be customized according to different needs, has a simple process, and is easy to scale.
[0027] Preferably, the concentration of the alkaline solution in step (1) is 0.005-0.15 mol / L, for example, 0.005 mol / L, 0.008 mol / L, 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.13 mol / L or 0.15 mol / L, etc., preferably 0.008-0.12 mol / L, more preferably 0.01-0.08 mol / L.
[0028] Preferably, the alkali in the alkaline solution in step (1) comprises at least one of NaOH and KOH.
[0029] Preferably, in step (1), the aluminum powder is placed in an alkaline solution, stirred for 0.2-10 min (for example, 0.2 min, 0.5 min, 0.8 min, 1 min, 1.5 min, 2 min, 2.5 min, 2.7 min, 3 min, 5 min, 7 min, 8 min, 9 min or 10 min, etc.) and subjected to ultrasonic treatment, and the stirring time is preferably 0.5-6 min.
[0030] In one embodiment, ultrasonic treatment is performed while stirring, and the stirring time is the same as the ultrasonic time, for example, the time is 0.2-10 min, preferably 0.5-6 min.
[0031] Preferably, the frequency of the ultrasonic treatment in step (1) is 50-100 Hz, for example, 50 Hz, 55 Hz, 60 Hz, 65 Hz, 70 Hz, 75 Hz, 80 Hz, 85 Hz, 90 Hz, 95 Hz or 100 Hz.
[0032] Preferably, after the ultrasonic treatment in step (1), water is quickly added for washing, and the pretreated aluminum powder is separated.
[0033] Preferably, the ammonium salt in step (2) includes at least one of ammonium sulfate, ammonium chloride and ammonium nitrate.
[0034] Preferably, the mass percentage of the ammonium salt in the reaction solution in step (2) is 1wt%-20wt%, for example, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%, 12wt%, 14wt%, 15wt%, 17wt%, 18wt% or 20wt%, etc.
[0035] Preferably, the nickel salt in step (2) includes at least one of nickel sulfate, nickel chloride and nickel nitrate.
[0036] Preferably, the mass percentage of the nickel salt in the reaction solution in step (2) is 3wt%-40wt%, for example, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 13wt%, 14wt%, 16wt%, 20wt%, 22wt%, 25wt%, 27wt%, 30wt%, 33wt%, 36wt% or 40wt%, etc.
[0037] Preferably, the additive in step (2) comprises a dispersant and a catalyst, and the catalyst comprises a mixture of palladium chloride and at least one of alizarin and anthraquinone.
[0038] Preferably, in the additive of step (2), the mass percentage of the dispersant is 0.5-5%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0039] Preferably, in the additive of step (2), the mass percentage of the catalyst is 95-99.5%, for example, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99% or 99.5%, etc.
[0040] Preferably, the content of palladium chloride accounts for 1-30% of the total mass of the catalyst, such as 1%, 2%, 3%, 5%, 7%, 9%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 27% or 30%, etc., preferably 5-20%.
[0041] Preferably, the dispersant is an inorganic dispersant, and the inorganic dispersant includes sodium hexametaphosphate.
[0042] Preferably, the mass percentage of the additive in step (2) in the reaction solution is 0.05-0.5%, for example, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, etc.
[0043] Preferably, in step (2), the pH is adjusted to be greater than 8.5, for example, 8.6, 8.8, 9.0, 9.3, 9.5, 9.6, 9.8, 10.0, 10.5, 11.0, 11.5, 11.8 or 12.0, etc.
[0044] Preferably, the pH is adjusted using aqueous ammonia.
[0045] Preferably, after adjusting the pH, the solution is pretreated to obtain the reaction solution, wherein the solution pretreatment includes: heating and ultrasonication under water bath conditions. Through this operation, the active sites on the surface of the aluminum powder can be increased at the initial stage of the reaction, the density and uniformity of the nickel layer coated on its surface can be improved, and the interface bonding strength between aluminum and nickel can be further improved, thereby improving the coating efficiency and the quality of the product.
[0046] Preferably, in the step of pre-treating the solution, the temperature is raised to 50-95°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C. ;
[0047] Preferably, in the step of pretreating the solution, the frequency of ultrasound is 50-200 Hz, for example, 50 Hz, 55 Hz, 60 Hz, 65 Hz, 70 Hz, 75 Hz, 80 Hz, 85 Hz, 90 Hz, 95 Hz, 100 Hz, 120 Hz, 130 Hz, 140 Hz, 160 Hz, 180 Hz or 200 Hz, etc.
[0048] Preferably, in the step of pretreating the solution, the ultrasonic time is 5 min-30 min, for example, 5 min, 10 min, 12 min, 15 min, 18 min, 20 min, 23 min, 24 min, 25 min, 27 min or 30 min, etc.
[0049] Preferably, in step (3), the reaction solution is transferred to a high-pressure container and stirred at a stirring rate of 300-1200 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1050 rpm, 1100 rpm or 1200 rpm, etc.
[0050] Preferably, the temperature of the high pressure liquid phase reduction reaction in step (3) is 120-200°C, for example, 120°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0051] Preferably, the gas pressure in the high-pressure liquid-phase reduction reaction in step (3) is 1.5-5 MPa, for example, 1.5 MPa, 1.7 MPa, 2 MPa, 2.3 MPa, 2.5 MPa, 2.7 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa or 5 MPa, etc., preferably 1.8-4.8 MPa.
[0052] Preferably, the reducing gas in step (3) comprises hydrogen.
[0053] In the present invention, high-pressure hydrogen can be used as the reducing gas.
[0054] Preferably, in step (3), a protective gas is also introduced into the high-pressure container, and the volume ratio of the reducing gas to the protective gas is (85-99%):(1-15%), wherein the volume percentage of the two is based on the total volume of the two as 100%, and the selection range of the reducing gas "85-99%" can be, for example, 85%, 87%, 88%, 89%, 90%, 92%, 93%, 95%, 97% or 99%, etc.
[0055] Preferably, the protective gas comprises at least one of nitrogen, helium or argon.
[0056] In the present invention, a mixed gas of reducing gas and protective gas is charged during the high-pressure liquid-phase reduction reaction, which is different from simply charging reducing gas (such as high-pressure hydrogen) and has the following advantages: on the one hand, it reduces the danger of reactions under high temperature and high pressure; on the other hand, the charging pressure can be appropriately increased, so that under high temperature conditions, the percentage of molecules and ions with higher energy is greatly increased, the collision energy is increased, the collision opportunities are expanded, and the reaction is accelerated.
[0057] Preferably, the preparation method further comprises the steps of washing, separating, drying and screening the product after the high pressure liquid phase reduction reaction.
[0058] Preferably, the washing liquid used in the washing is at least one of distilled water, deionized water and ethanol.
[0059] Preferably, the drying temperature is 100-160°C, such as 100°C, 110°C, 120°C, 130°C, 150°C or 160°C.
[0060] In a third aspect, the present invention provides a use of the core-shell structure composite powder as described in the first aspect, wherein the core-shell structure composite powder is used in at least one of the fields of railways, aviation, electric power, chemical industry, petroleum, automobiles or metallurgy.
[0061] Preferably, the core-shell structure composite powder is used as at least one of a thermal spraying material, a metal-ceramic composite material, an organic chemical catalyst, a high-temperature alloy powder molding material, a solid fuel, and an electromagnetic shielding conductive filler.
[0062] Since nickel and aluminum can produce a strong alloying exothermic reaction during spraying and can form a strong coating on the substrate surface by metallurgical bonding, the core-shell structure composite powder of the present invention is particularly suitable for application in the field of spraying and has broad application prospects.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention utilizes a nickel layer to coat aluminum powder. During spraying, nickel and aluminum can produce a strong exothermic alloying reaction and can form a strong coating on the substrate surface in a metallurgical bonding manner. Therefore, the core-shell structure composite powder of the present invention is particularly suitable for application in the field of spraying and has broad application prospects.
[0066] (2) The present invention adopts a method combining sonication and high temperature liquid phase pressure reduction reaction to prepare a core-shell structured nickel-coated aluminum composite powder. The prepared product has stable performance and can be customized according to different needs. The process is simple and easy to scale up. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0068] Example 1
[0069] This embodiment provides a core-shell structure nickel-coated aluminum composite powder, and the preparation method thereof comprises the following steps:
[0070] (1) Aluminum powder pretreatment: The aluminum powder was placed in a 0.05 mol / L NaOH aqueous solution, rapidly stirred and ultrasonically treated at a frequency of 80 Hz for 1 min, then rapidly washed with water for multiple times, filtered and set aside;
[0071] (2) dispersing the aluminum powder filtered in step (1) in deionized water, adding ammonium salt (ammonium sulfate), nickel salt (nickel sulfate), additives (including dispersants and catalysts, the dispersant is sodium hexametaphosphate, the catalyst is a mixture of palladium chloride and alizarin, the content of the dispersant accounts for 1% of the total mass of the additives, the content of the catalyst accounts for 99% of the total mass of the additives, and the content of palladium chloride accounts for 20% of the total mass of the catalyst), quickly stirring evenly, adding ammonia water to adjust the solution pH to 9.5, to obtain a reaction solution, wherein the mass percentage of ammonium salt in the reaction solution is 10wt%, the mass percentage of nickel salt is 30wt%, and the mass percentage of additive is 0.1%;
[0072] The reaction solution was heated to 75°C in a water bath and subjected to ultrasonic treatment at a frequency of 100 Hz for 10 min;
[0073] (3) The solution after ultrasonic treatment in step (2) is transferred to a high-pressure container, stirred at a rate of 800 rpm, the air in the high-pressure container is replaced with nitrogen, and then heated to 150° C., and a mixture of high-purity hydrogen and high-purity argon is added (wherein the volume percentage of hydrogen is 99% and the volume percentage of argon is 1%), and the gas pressure is 4.8 MPa. After the reaction is complete, the temperature is stopped, the gas is released, and the reactants are washed and filtered in deionized water for multiple times, dried in an oven at 120° C., and sieved to obtain a core-shell structured nickel-coated aluminum composite powder.
[0074] Example 2
[0075] This embodiment provides a core-shell structure nickel-coated aluminum composite powder, and the preparation method thereof comprises the following steps:
[0076] (1) Aluminum powder pretreatment: The aluminum powder was placed in a 0.08 mol / L NaOH aqueous solution, rapidly stirred and ultrasonically treated at a frequency of 100 Hz for 2 min, then rapidly washed with water for multiple times, filtered and set aside;
[0077] (2) dispersing the aluminum powder filtered in step (1) in deionized water, adding ammonium salt (ammonium sulfate), nickel salt (nickel chloride), and additives (including a dispersant and a catalyst, wherein the dispersant is sodium hexametaphosphate, and the catalyst is a mixture of palladium chloride and anthraquinone, the content of the dispersant accounts for 3% of the total mass of the additive, the content of the catalyst accounts for 97% of the total mass of the additive, and the content of palladium chloride accounts for 10% of the total mass of the catalyst), rapidly stirring the mixture to be uniform, adding ammonia water to adjust the pH value of the solution to 10.5, and obtaining a reaction solution, wherein the mass percentage of the ammonium salt in the reaction solution is 5wt%, the mass percentage of the nickel salt is 10wt%, and the mass percentage of the additive is 0.2%;
[0078] The reaction solution was heated to 90°C in a water bath and subjected to ultrasonic treatment at a frequency of 75 Hz for 20 min;
[0079] (3) The solution after ultrasonic treatment in step (2) is transferred to a high-pressure container, stirred at a rate of 1000 rpm, the air in the high-pressure container is replaced with nitrogen, and then heated to 180° C., and a mixture of high-purity hydrogen and high-purity argon is added at the same time (wherein the volume percentage of hydrogen is 98% and the volume percentage of argon is 2%), and the gas pressure is 2 MPa. After the reaction is complete, the temperature is stopped, the gas is released, and the reactant is washed and filtered in deionized water for multiple times, dried in an oven at 130° C., and sieved to obtain a core-shell structured nickel-coated aluminum composite powder.
[0080] Example 3
[0081] This embodiment provides a core-shell structure nickel-coated aluminum composite powder, and the preparation method thereof comprises the following steps:
[0082] (1) Aluminum powder pretreatment: The aluminum powder was placed in a 0.02 mol / L NaOH aqueous solution, rapidly stirred and ultrasonically treated at a frequency of 60 Hz for 4 min, then rapidly washed with water for multiple times, filtered and set aside;
[0083] (2) dispersing the aluminum powder filtered in step (1) in deionized water, adding ammonium salt (ammonium nitrate), nickel salt (nickel nitrate), additives (including dispersants and catalysts, the dispersant is sodium hexametaphosphate, the catalyst is a mixture of palladium chloride and alizarin, the content of the dispersant accounts for 4.5% of the total mass of the additives, the content of the catalyst accounts for 95.5% of the total mass of the additives, and the content of palladium chloride accounts for 15% of the total mass of the catalyst), quickly stirring evenly, adding ammonia water to adjust the solution pH to 9, and obtaining a reaction solution, wherein the mass percentage of ammonium salt in the reaction solution is 15wt%, the mass percentage of nickel salt is 20wt%, and the mass percentage of additives is 0.4%;
[0084] The reaction solution was heated to 80°C in a water bath and subjected to ultrasonic treatment at a frequency of 150 Hz for 25 min;
[0085] (3) The solution after ultrasonic treatment in step (2) is transferred to a high-pressure container, stirred at a rate of 400 rpm, the air in the high-pressure container is replaced with nitrogen, and then heated to 120° C., and a mixture of high-purity hydrogen and high-purity argon is added (wherein the volume percentage of hydrogen is 97% and the volume percentage of argon is 3%), and the gas pressure is 3.8 MPa. After the reaction is complete, the temperature is stopped, the gas is released, and the reactant is washed and filtered in deionized water for multiple times, dried in an oven at 100° C., and sieved to obtain a core-shell structured nickel-coated aluminum composite powder.
[0086] Example 4
[0087] This embodiment provides a core-shell structure nickel-coated aluminum composite powder, and the preparation method thereof comprises the following steps:
[0088] (1) Aluminum powder pretreatment: The aluminum powder was placed in a 0.1 mol / L NaOH aqueous solution, rapidly stirred and ultrasonically treated at a frequency of 50 Hz for 8 min, then rapidly washed with water for multiple times, filtered and set aside;
[0089] (2) dispersing the aluminum powder filtered in step (1) in deionized water, adding ammonium salt (ammonium chloride), nickel salt (nickel sulfate), additives (including dispersants and catalysts, the dispersant is sodium hexametaphosphate, the catalyst is a mixture of palladium chloride and anthraquinone, the content of the dispersant accounts for 0.5% of the total mass of the additives, the content of the catalyst accounts for 99.5% of the total mass of the additives, and the content of palladium chloride accounts for 30% of the total mass of the catalyst), quickly stirring evenly, adding ammonia water to adjust the solution pH to 11, and obtaining a reaction solution, wherein the mass percentage of ammonium salt in the reaction solution is 20wt%, the mass percentage of nickel salt is 5wt%, and the mass percentage of additives is 0.5%;
[0090] The reaction solution was heated to 60°C in a water bath and subjected to ultrasonic treatment at a frequency of 175 Hz for 5 min;
[0091] (3) The solution after ultrasonic treatment in step (2) is transferred to a high-pressure container, stirred at a rate of 1100 rpm, the air in the high-pressure container is replaced with nitrogen, and then heated to 200° C., and a mixture of high-purity hydrogen and high-purity nitrogen is added (wherein the volume percentage of hydrogen is 97% and the volume percentage of nitrogen is 3%), and the gas pressure is 5 MPa. After the reaction is complete, the temperature is stopped, the gas is released, and the reactant is washed and filtered in deionized water for multiple times, dried in an oven at 100° C., and sieved to obtain a core-shell structured nickel-coated aluminum composite powder.
[0092] Example 5
[0093] This embodiment provides a core-shell structure nickel-coated aluminum composite powder, and the preparation method thereof comprises the following steps:
[0094] (1) Aluminum powder pretreatment: The aluminum powder was placed in a 0.15 mol / L NaOH aqueous solution, rapidly stirred for 3 min, ultrasonically treated at a frequency of 65 Hz, and then rapidly washed with water for multiple times, filtered and set aside;
[0095] (2) dispersing the aluminum powder filtered in step (1) in deionized water, adding ammonium salt (ammonium sulfate), nickel salt (nickel chloride), and additive (a mixture of sodium hexametaphosphate and alizarin, wherein the mass percentage of sodium hexametaphosphate in the mixture is 5%), rapidly stirring the mixture, and adding ammonia water to adjust the pH value of the solution to 9.5 to obtain a reaction solution, wherein the mass percentage of ammonium salt in the reaction solution is 2wt%, the mass percentage of nickel salt is 35wt%, and the mass percentage of additive is 0.05%;
[0096] The reaction solution was heated to 65°C in a water bath and subjected to ultrasonic treatment at a frequency of 60 Hz for 30 min;
[0097] (3) The solution after ultrasonic treatment in step (2) is transferred to a high-pressure container, stirred at a rate of 1000 rpm, the air in the high-pressure container is replaced with nitrogen, and then heated to 170° C., and a mixture of high-purity hydrogen and high-purity nitrogen is added (wherein the volume percentage of hydrogen is 88% and the volume percentage of nitrogen is 12%), and the gas pressure is 1.5 MPa. After the reaction is complete, the temperature is stopped, the gas is released, and the reactant is washed and filtered in deionized water for multiple times, dried in an oven at 100° C., and sieved to obtain a core-shell structured nickel-coated aluminum composite powder.
[0098] Example 6
[0099] The only difference between this embodiment and embodiment 1 is that the concentration of the NaOH aqueous solution in step (1) is 0.2 mol / L.
[0100] Example 7
[0101] The only difference between this embodiment and embodiment 1 is that in step (1), only rapid stirring is performed without ultrasonic action.
[0102] Example 8
[0103] The only difference between this embodiment and embodiment 1 is that in step (2), the content of palladium chloride accounts for 4% of the total mass of the catalyst.
[0104] Example 9
[0105] The only difference between this embodiment and embodiment 1 is that in step (2), the content of palladium chloride accounts for 22% of the total mass of the catalyst.
[0106] Example 10
[0107] The only difference between this embodiment and embodiment 1 is that in step (2), the content of the dispersant accounts for 0.3% of the total mass of the additive.
[0108] Embodiment 11
[0109] The only difference between this embodiment and embodiment 1 is that in step (2), the content of the dispersant accounts for 6% of the total mass of the additive.
[0110] Example 12
[0111] The only difference between this embodiment and embodiment 1 is that in step (2), the mass percentage content of the additive is 0.03%.
[0112] Example 13
[0113] The only difference between this embodiment and embodiment 1 is that in step (2), the mass percentage content of the additive is 0.6%.
[0114] Embodiment 14
[0115] The only difference between this embodiment and embodiment 1 is that in step (2), the reaction liquid is not pretreated (the reaction liquid is heated to 75° C. in a water bath and ultrasonically treated at a frequency of 100 Hz for 10 min), but the reaction liquid is directly transferred to a high-pressure container to perform step (3).
[0116] Embodiment 15
[0117] The only difference between this embodiment and embodiment 1 is that in step (3), the mixed gas of high-purity hydrogen and high-purity argon is replaced by high-purity hydrogen, and the gas pressure is 1.3 MPa.
[0118] Comparative Example 1
[0119] The only difference between this embodiment and embodiment 1 is that in step (3), the mixed gas of high-purity hydrogen and high-purity argon is replaced by high-purity hydrogen, and the gas pressure is 1.8 MPa.
[0120] The Hall flow velocity and bulk density of the composite powders of Examples 1-15 and Comparative Example 1 were tested. The test results are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] It can be seen from the comprehensive examples that the core-shell structured nickel-coated aluminum composite powder prepared in the examples of the present invention is completely coated, the nickel layer is uniform and has good bonding strength and fluidity. The surface coated nickel layer has high density and uniformity, and the product quality is good.
[0125] By comparing Example 1 with Example 6, it can be seen that the concentration of the NaOH solution has a preferred range. The concentration of the NaOH solution in Example 6 is too high, resulting in OH in the solution. - The concentration is high, which affects the reaction rate; there is a lot of fine powder, the loose density becomes smaller, and the Hall flow rate becomes larger.
[0126] By comparing Example 1 with Example 7, it can be seen that in the step of pre-treating with alkali solution, ultrasonic action is performed while stirring, which helps to make the chemical reaction more complete and the coating more uniform.
[0127] By comparing Example 1 with Examples 8-9, it can be seen that there is a preferred range for the content of palladium chloride in the catalyst. A range of 5-20% is more conducive to accelerating the chemical reaction, facilitating nickel reduction, and achieving more uniform coating.
[0128] By comparing Example 1 with Examples 10-11, it can be seen that there is a preferred range for the content of the dispersant. A range of 0.5-5% can better and effectively promote the uniform dispersion of the various components in the solution system, making the reaction process more uniform and the particle size of the nickel powder coated on the surface more uniform.
[0129] By comparing Example 1 with Examples 12-13, it can be seen that there is a preferred range for the content of the additive. Within the range of 0.05-0.5%, it is more conducive to making the chemical reaction proceed in the direction of reducing nickel, which is beneficial to improving the uniformity of coating and reducing the generation of fine powder.
[0130] By comparing Example 1 with Example 14, it can be seen that pre-treating the reaction solution after adjusting the pH helps to promote the uniformity of the reaction of the entire system, prepare a coating material with a relatively uniform particle size, and ensure that a coated powder with a high bulk density is obtained.
[0131] By comparing Example 1 with Example 15, it can be seen that filling a mixed gas of reducing gas and protective gas during the high-pressure liquid-phase reduction reaction is more beneficial to nickel reduction if the ratio of the gas is well controlled than simply flushing in reducing gas. However, if the pressure is too low, it is difficult to obtain a good coated powder, and the reaction speed is very slow, which is not conducive to industrial application.
[0132] By comparing Example 1 with Comparative Example 1, it can be seen that when the reducing gas is filled into the high-pressure liquid phase reduction reaction, if the pressure of the system is too low, it is very unfavorable for the reduction reaction to proceed. Not only can the ideal nickel-coated powder not be obtained, but also due to the slow reaction speed, it is not conducive to industrial application and promotion.
[0133] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A core-shell structure composite powder, characterized in that: The core-shell structure composite powder is a core-shell structure nickel-coated aluminum composite powder, and the core-shell structure composite powder comprises a core aluminum powder and a shell nickel layer coated on the surface of the core aluminum powder.
2. The core-shell structure composite powder according to claim 1, characterized in that: The core aluminum powder includes at least one of spherical particles, quasi-spherical particles, rod-shaped materials or flake materials; Preferably, the diameter of the spherical particles is 1-125 μm, preferably 5-120 μm, and more preferably 8-105 μm; Preferably, the diameter of the spherical particles is 1-125 μm, preferably 5-120 μm, and more preferably 8-105 μm; Preferably, the diameter of the rod-shaped material is 1-125 μm, preferably 5-120 μm, and more preferably 10-110 μm; Preferably, the length of the rod-shaped material is 1-200 μm, preferably 10-160 μm, and more preferably 10-130 μm; Preferably, the diameter of the sheet material is 1-125 μm, preferably 5-120 μm, and more preferably 10-110 μm; Preferably, the thickness of the sheet material is 1-20 μm, preferably 2-15 μm, and more preferably 5-10 μm.
3. The core-shell structure composite powder according to claim 1 or 2, characterized in that: The outer shell nickel layer is evenly coated on the surface of the inner core aluminum powder; Preferably, the core-shell structure composite powder is completely coated, the nickel layer is uniform and has good bonding strength and fluidity.
4. The core-shell structure composite powder according to any one of claims 1 to 3, characterized in that: The mass percentage of the core aluminum powder to the core-shell structure composite powder is 4-98%; Preferably, the mass percentage of the outer shell nickel layer in the core-shell structure composite powder is 2-96%, preferably 20-95%.
5. A method for preparing a core-shell structure composite powder according to any one of claims 1 to 4, characterized in that: The core-shell structure composite powder is prepared by a method combining sonochemistry and high-pressure liquid phase reduction, and the method comprises the following steps: (1) Aluminum powder pretreatment: placing aluminum powder in an alkaline solution for ultrasonic treatment to obtain pretreated aluminum powder; (2) mixing the pretreated aluminum powder with an ammonium salt, a nickel salt, an optional additive and a solvent, adjusting the pH, and obtaining a reaction solution; (3) The reaction solution is transferred to a high-pressure container, and a high-pressure liquid-phase reduction reaction is carried out under the condition of introducing a reducing gas to obtain the core-shell structure composite powder.
6. The method for preparing the core-shell structure composite powder according to claim 5, characterized in that: The concentration of the alkaline solution in step (1) is 0.005-0.15 mol / L, preferably 0.008-0.12 mol / L, more preferably 0.01-0.08 mol / L; Preferably, the alkali in the alkaline solution in step (1) comprises at least one of NaOH and KOH; Preferably, in step (1), the aluminum powder is placed in an alkaline solution, stirred for 0.2-10 min and subjected to ultrasonic treatment, and the stirring time is preferably 0.5-6 min; Preferably, the frequency of the ultrasonic treatment in step (1) is 50-100 Hz; Preferably, after the ultrasonic treatment in step (1), water is quickly added for washing, and the pretreated aluminum powder is separated.
7. The method for preparing the core-shell structure composite powder according to claim 5 or 6, characterized in that: The ammonium salt in step (2) includes at least one of ammonium sulfate, ammonium chloride and ammonium nitrate; Preferably, the mass percentage of the ammonium salt in the reaction solution in step (2) is 1wt%-20wt%; Preferably, the nickel salt in step (2) comprises at least one of nickel sulfate, nickel chloride and nickel nitrate; Preferably, the mass percentage of the nickel salt in the reaction solution in step (2) is 3wt%-40wt%; Preferably, the additive in step (2) comprises a dispersant and a catalyst, and the catalyst comprises a mixture of palladium chloride and at least one of alizarin and anthraquinone; Preferably, in the additive of step (2), the mass percentage of the dispersant is 0.5-5%; Preferably, in the additive of step (2), the mass percentage of the catalyst is 95-99.5%; Preferably, the content of palladium chloride accounts for 1-30% of the total mass of the catalyst, preferably 5-20%; Preferably, the dispersant is an inorganic dispersant, and the inorganic dispersant includes sodium hexametaphosphate; Preferably, the mass percentage of the additive in step (2) in the reaction solution is 0.05-0.5%; Preferably, in step (2), the pH is adjusted to be greater than 8.5, Preferably, the pH is adjusted using aqueous ammonia; Preferably, after adjusting the pH, the solution is pretreated to obtain the reaction solution, wherein the solution pretreatment comprises: heating and ultrasonication under water bath conditions; Preferably, in the solution pretreatment step, the temperature is raised to 50-95°C; Preferably, in the solution pretreatment step, the frequency of ultrasound is 50-200 Hz; Preferably, in the solution pretreatment step, the ultrasonic time is 5 min-30 min.
8. The method for preparing the core-shell structure composite powder according to any one of claims 5 to 7, characterized in that: In step (3), the reaction solution is transferred to a high pressure container and stirred at a stirring rate of 300-1200 rpm; Preferably, the temperature of the high pressure liquid phase reduction reaction in step (3) is 120-200°C; Preferably, the gas pressure in the high-pressure liquid-phase reduction reaction in step (3) is 1.5-5 MPa, preferably 1.8-4.8 MPa; Preferably, the reducing gas in step (3) comprises hydrogen; Preferably, in step (3), a protective gas is also introduced into the high-pressure container, and the volume ratio of the reducing gas to the protective gas is (85-99%):(1-15%); Preferably, the protective gas comprises at least one of nitrogen, helium or argon.
9. The method for preparing the core-shell structure composite powder according to any one of claims 5 to 8, characterized in that: The preparation method further comprises the steps of washing, separating, drying and screening the product after the high pressure liquid phase reduction reaction; Preferably, the drying temperature is 100-160°C.
10. Use of the core-shell structure composite powder according to any one of claims 1 to 4, characterized in that: The core-shell structure composite powder is used in at least one of the fields of railway, aviation, electric power, chemical industry, petroleum, automobile or metallurgy; Preferably, the core-shell structure composite powder is used as at least one of a thermal spraying material, a metal-ceramic composite material, an organic chemical catalyst, a high-temperature alloy powder molding material, a solid fuel, and an electromagnetic shielding conductive filler.
Citation Information
Cited By
Nickel-coated aluminum powder with high specific surface area, preparation method and hydrogen production method
CN120362479A
Conductive nickel powder / aluminum powder composite powder and preparation method thereof
CN120438615A